Apathy and white matter integrity in amnestic mild cognitive impairment: A whole brain analysis with tract‐based spatial statistics: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Setiadi, Tania M; Opmeer, Esther M; Martens, Sander; Marsman, Jan‐Bernard C; Tumati, Shankar; Reesink, Fransje E; De Deyn, Peter Paul; Aleman, André; Ćurčić‐Blake, Branislava
Abstract: Background: Apathy is one of the most prevalent neuropsychiatric symptoms in amnestic mild cognitive impairment (aMCI) and is associated with an increased risk for progression to Alzheimer's Disease (AD). Previous diffusion tensor imaging (DTI) studies in AD have shown that apathy is associated with changes in the cingulum, corpus callosum and uncinate fasciculus (Hahn et al., 2013; Kim et al., 2011). However, the underlying white matter (WM) correlates of apathy in aMCI are still unclear. Therefore, we aimed to investigate the association between the severity of apathy and white matter integrity in aMCI using diffusion tensor imaging (DTI) and tract‐based spatial statistics (TBSS). Method: Twenty‐nine aMCI patients and 20 cognitively healthy controls were included. Apathy severity was assessed with the Apathy Evaluation Scale Clinician version (AES‐C). Depressive symptoms were assessed using the Geriatric Depression Scale (GDS). We calculated a sub‐score of the GDS (i.e. GDS non‐apathy) which excluded apathy‐related items (Adams et al., 2004). We applied whole‐brain TBSS analyses to all DTI parameters: i.e. fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD), investigating which WM areas were associated with apathy severity. Age, gender, MMSE, and GDS non‐apathy were used as covariates. Significance was set to p < .05, corrected for multiple comparisons using Threshold‐Free Cluster Enhancement (TFCE). Result: There was no statistical difference between groups on age, gender, education level, MMSE, and AES‐C scores. Group comparison TBSS analyses showed that the aMCI group did not differ in any of the DTI parameters compared to the control group. Within the aMCI group, significant inverse associations were observed between AES‐C scores and FA values in the bilateral genu and body of the corpus callosum, anterior and superior corona radiata, anterior thalamic radiation, anterior part of inferior frontooccipital fasciculus, and the right forceps minor, superior longitudinal fasciculus/arcuate fasciculus anterior segment, corticospinal tract/internal capsule ( pTFCE < .05). A similar pattern was observed in the combined group of aMCI and controls ( pTFCE < .025). Conclusion: There was no significant WM integrity difference between aMCI and control groups. Our findings point to reduced integrity in widely distributed WM pathways being related to apathy severity, regardless of aMCI diagnosis.